2018
DOI: 10.1080/17482631.2018.1479581
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ perspectives on everyday life with obesity: a qualitative study

Abstract: Care providers need to be skilled in assessing each individual's resources and interpretations of their condition, to be able to communicate in a respectful, patient-centred manner and to assist adolescents to explore their ambivalence and set their own realistic goals. More research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…Many studies have revealed association between obesity and diseases such as cardiovascular disease, diabetes, and hypertension. [7101112131415] Besides, low self-esteem[10141519] and disturbance in mental functions[25] are also associated with obesity. Although these unfavorable consequences of obesity threaten a person, their effects are significant on family and community.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have revealed association between obesity and diseases such as cardiovascular disease, diabetes, and hypertension. [7101112131415] Besides, low self-esteem[10141519] and disturbance in mental functions[25] are also associated with obesity. Although these unfavorable consequences of obesity threaten a person, their effects are significant on family and community.…”
Section: Discussionmentioning
confidence: 99%
“…[39] Other researchers also believe that obesity decreases physical activity and increases passive activity. [1340] In sum, changing the pattern of leisure and using a stagnant and individualist process of leisure rather than an attractive and collectivist leisure plays a role in the persistence of obesity and the emergence of wider implications because of a defective cycle in which obesity reduce physical activity, and this condition is once again effective in maintaining obesity. It also reduces family and social relationships, and imposes psychological pressure on people, prevents everyday activities and can challenge the whole life of the individual.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations